Innovative Approaches in the Management of Chronic Periodontitis: Clinical and Microbiological Perspectives - Elnazarov Azamat Toʻlqin oʻgʻli (American Journal of Biomedicine and Pharmacy, 2025)
Chronic periodontitis is a multifactorial inflammatory disease that leads to the progressive destruction of the periodontal ligament and alveolar bone, ultimately resulting in tooth loss if left untreated. This article explores advanced therapeutic strategies in the clinical and microbiological management of chronic periodontitis. Emphasis is placed on novel antimicrobial agents, host modulation therapy, regenerative procedures, and the integration of diagnostics such as microbial profiling and biomarkers. A comprehensive clinical study is presented, along with a critical analysis of current evidence supporting these interventions. The findings suggest that individualized, evidence-based treatments targeting both microbial and host response yield superior clinical outcomes. Chronic periodontitis is a widespread, progressive inflammatory disease characterized by the destruction of the tooth-supporting structures, including periodontal ligament and alveolar bone. Affecting over 740 million individuals globally, this condition not only compromises oral function but also contributes to systemic inflammation and is associated with cardiovascular disease, diabetes, and adverse pregnancy outcomes. Traditional management primarily involves mechanical debridement; however, emerging evidence supports the adjunctive use of pharmacological and immunomodulatory agents. This article provides a comprehensive analysis of advanced therapeutic strategies in periodontitis management, including localized antimicrobial agents, systemic antibiotics, host modulation therapy (HMT), and regenerative techniques such as guided tissue regeneration (GTR) and enamel matrix derivatives (EMD). Additionally, microbiological diagnostic tools and biomarker profiling are discussed in detail to support precision-based personalized treatment. Clinical outcomes from a longitudinal study involving 150 patients demonstrate that integrated treatment approaches significantly outperform standard scaling and root planing (SRP) alone. Microbial reduction and modulation of inflammatory biomarkers such as IL-1β and MMP-8 resulted in improved periodontal attachment and reduced disease recurrence. These findings underscore the importance of combining clinical, microbiological, and biochemical strategies for long-term success in managing chronic periodontitis.